Skill-biased labor market reforms and international competitiveness - Hans-Jörg Schmerer (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2012)
This paper proposes a multi-industry trade model with integrated capital and goods markets. Labor market imperfections in line with Mortensen and Pissarides (1994) give rise to unemployment and a channel for the government to influence markets through institutional changes. Labor market interventions feedback into the product market through changes in a country's competitiveness. Moreover, the distinction between high- and low-skill workers facilitates the analysis of skill-biased institutional changes that have stronger impact on certain skill groups. The comparative static exercise in this paper shows that high-skilled benefit from low-skill biased labor market reforms through higher wages. Lower labor costs reduce unemployment of the low-skilled and increases the reforming country's competitiveness. One-sided labor market interventions have feedback effects through adjustments at the extensive margin, which affect all workers at home and abroad irrespective of their level of skill. Governments in the non-reforming countries may react to this loss in competitiveness by initiating cooperative labor market reforms instead. – – Dieses Papier untersucht mögliche Auswirkungen von Arbeitsmarktreformen in einem Mehrsektorenmodell mit imperfekten Arbeitsmärkten auf Grund von Suchfriktionen. Im Rahmen des Modells beeinflussen Arbeitsmarktinstitutionen die internationale Wettbewerbsfähigkeit einer Ökonomie. Eine Verringerung des Arbeitslosengeldes beispielsweise kann die Wettbewerbsfähigkeit eines Landes über eine Reduktion der Produktionskosten erhöhen. Die Unterscheidung zwischen hochund niedrigqualifizierten Arbeitnehmern erlaubt darüberhinaus die Analyse von einseitigen, bestimmte Bildungsgruppen betreffende, Arbeitsmarktreformen. Es wird gezeigt, dass hochqualifizierte Arbeitnehmer durch Arbeitsmarktreformen, die ins Besondere niedrigqualifizierte Arbeitnehmer betreffen, von höheren Lohnzahlungen profitieren. Durch die Verschiebung des komparativen Vorteils beeinflussen einseitige Arbeitsmarktreformen den Arbeitsmarkt sowohl im Inland als auch im Ausland.
Keywords: F16; E24; J6; F21; 330; FDI; search unemployment; labor market institutions; Direktinvestition; Globalisierung; Arbeitsmarktpolitik; Beschäftigungseffekt; Institutioneller Wandel; Theorie der Arbeitslosigkeit; Internationaler Wettbewerb; Suchtheorie